Unusual meningitis caused by non-typhoid Salmonella in an Italian infant: a case report - Ficara, Monica; Cenciarelli, Valentina; Montanari, Lisa; Righi, Beatrice; Fontjin, Simone; Cingolani, Greta; Predieri, Barbara; Berardi, Alberto; Lucaccioni, Laura; Iughetti, Lorenzo (Acta Biomedica Atenei Parmensis, 2019)
Background: Non-typhoid Salmonella (NTS) is an important cause of bacterial meningitis in newborn and infants in developing countries, but rarely in industrialized ones. We describe an unusual presentation of bacterial meningitis in an infant, focusing on his diagnostic and therapeutic management. Case report: An Italian two-month old male presented high fever and diarrhea with blood, associated with irritability. Inflammatory markers were high, cerebrospinal fluid analysis was compatible with bacterial meningitides but microbiological investigations were negative. Salmonella enteritidis was isolated from blood. Cerebral ultrasound and MRI showed periencephalic collection of purulent material. Specific antibiotic therapy with cefotaxime was initiated with improvement of clinical conditions and blood tests. Brain MRI follow up improved progressively. Conclusions: Most of pediatric patients with NTS infection develop self-limited gastroenteritis, but in 3-8% of the cases complications such as bacteremia and meningitis may occur, especially in weak patients. Cerebral imaging can be useful to identify neurological findings. Although there is no standardized treatment for this condition, specific antibiotic therapy for at least four weeks is recommended. Neuroimaging follow up is required due to high risk of relapse.